METHODS OF CONCENTRATION OF FRUIT JUICES AND THEIR ANALYSIS - Aripova, Kamola (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The paper considers the process of evaporation of water in multi-body vacuum evaporation plants to optimize the concentration of fruit juices. An analysis of the designs of vacuum evaporation plants for food concentration is given. Based on empirical dependencies and mathematical modeling, the optimal dynamics of the process is determined, which makes it possible to calculate the evaporation parameters to minimize energy consumption, as well as improve the quality of the finished product and reduce oxymethylfurfural. The results of the research can be used to economically optimize the technology, increasing productivity and efficiency of production processes.